Biofilms in Chronic Wounds: Pathogenesis and Diagnosis - Wu, Yuan-Kun; Cheng, Nai-Chen; Cheng, Chao-Min (Trends in biotechnology (Regular ed.), 2019)
Chronic non-healing wounds have become a major worldwide healthcare burden. The impact of biofilms on chronic wound infection is well established. Despite increasing understanding of the underlying mechanism of biofilm formation in chronic wounds, current strategies for biofilm diagnosis in chronic wounds are still far from ideal. In this review, we briefly summarize the mechanism of biofilm formation and focus on current diagnostic approaches of chronic wound biofilms based on morphology, microbiology, and molecular assays. Innovative biotechnological approaches, such as wound blotting and transcriptomic analysis, may further shed light on this unmet clinical need. The continuous development of these sophisticated diagnostic approaches can markedly contribute to the future implementation of point-of-care biofilm detection in chronic wound care. The impact of biofilms on delayed wound healing has drawn increasing attention. Their importance led to the establishment of biofilm-based wound care where chronic wounds are treated using multipronged strategies to remove biofilms over wound beds to facilitate the recovery of epithelial integrity. Current clinical and preclinical diagnostic techniques fail to accurately identify pathogens and the precise location of biofilms over wound surfaces, rendering timely medical or surgical intervention to eradicate biofilms elusive. Wound blotting is a novel biotechnology that predicts wound outcomes and localizes biofilms on wound surfaces by determining the distribution pattern of tumor necrosis factor-alpha (TNF-α) and biofilm mucopolysaccharides. The rapid and objective analysis offered by this technique may assist clinicians in treating chronic wound biofilms.